Competitiveness as the main factor of enterprise development in modern conditions (Economics and region, 2023)
Today it is more important than ever for a company to be a leader. By occupying a leading position in the market, an organization has access to the best resources, has more possible ways of development and, consequently, receives greater rewards compared to its competitors. However, it is worth understanding that market leadership also involves increased responsibility towards consumers and partners, as well as increasing risks that may arise during economic activity. A leading company does not appear out of nowhere; it earns its reputation in the competitive conditions that are an essential component of any modern market environment. Competition is the basis of competitiveness. The last one characterizes the ability of an enterprise to satisfy customer demands more successfully and have a certain competitive advantage. Ukrainian companies are mostly far from having a high level of competitiveness. This is due to numerous problems, including technological backwardness, low investment attractiveness or even imperfect management systems. However, in the conditions of globalization, conducting military operations within the country's territory, European integration, economic crisis and political instability, it is becoming much more difficult for enterprises to create a proper competitive environment and achieve high competitiveness. All of these increase the interest in studying competitiveness as a crucial category in modern economic science and determining ways to improve it for domestic economic entities. Thus, the study proved the importance of forming a high competitive level of an enterprise for its viability. The authors also state that international cooperation, financing, innovation and technological development and the choice of modern company management methodologies can be identified as areas for improving competitiveness. In addition, the article emphasizes the need to create a decent country brand. The last one is commonly understood as the combination of diverse characteristic features and exactly their symbiosis actually reflects the state's perception of itself as an autonomous unit of the international community with its peculiarities and advantages. Therefore, proper country branding will not only enhance the country's image in the global market but also contribute to the recovery and prosperity of domestic entrepreneurship.
Keywords: competitiveness; development strategies; war; global transformations; international cooperation; country brand